The problem of divers, aviators and paratroopers - barotrauma of the paranasal sinuses - Adamczyk, Katarzyna; Adamczyk, Dorota; Wójcik, Rafał (Journal of Education, Health and Sport, 2018)
Barotrauma of the paranasal sinuses is a trauma caused by a large difference in air pressure between the sinuses and the environment. It concerns essentially divers, aviators, as well as paratroopers. A characteristic symptom is sudden and piercing pain in the sinus area. The pain begins while the ambient's pressure is changing or an instant later. The result of a pressure injury may be an epistaxis. Sinusitis may be also an effect of sinuses' mucosal damage. Drugs used primarily in patients with pressure-related injury are vasoconstructive medicaments and analgesics. Antibiotics are also applied in some situations. Because the incidence of barotrauma increases in predisposed people, e.g. with anatomical abnormalities, nose surgery, including correction of the nasal septum or paranasal sinuses, i.e. conchotomy, is used to prevent injury.